Analysis of Determinants of Capital Expenditure Allocation in West Sumatra Province - rahayu, resti (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2019)
This study aims to analyze the effect of Regional Original Revenue, Balancing Funds, and financing surplus budget on Regency / City Capital Expenditures in West Sumatra Province in 2011 - 2017. Data used in this research is secondary data. To analyze the influence of PAD, Perimbanagan Funds, and SILPA on district/city Capital Expenditures in West Sumatra Province in 2011-2017, a panel data regression analysis method is used, which is a combination of inter-location data (cross section) and data from 19 districts / cities in Sumatra West and time series data with annual data from 2011-2017. The results of the study show that the right regression model used is the fixed effect model. With the results namely thevariable Original Regional Income has a positive effect on district / city capital expenditure in West Sumatra Province in 2011- 2017, while the Balancing Fund has a positive effect on district / city capital expenditure in West Sumatra Province in the year 2011 - 2017, and the financing surplus budget variable positive affects the Regency / City capital expenditure inWest Sumatra Province in 2011 - 2017. Keywords: Regional Expenditures, Regional Original Revenue, Balancing Funds, Financing Surplus Budget. JEL: P48; R10